2019
DOI: 10.1039/c9ta06251c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient piezo-catalytic hydrogen peroxide production from water and oxygen over graphitic carbon nitride

Abstract: Efficient H2O2 production directly from water and oxygen via a piezo-catalytic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 34 publications
0
68
1
Order By: Relevance
“…More accurately, Au or Ag deposition under ultrasonic proved the existing of polarization along [001] direction, as the metals were found to be distributed on the edges of Mo 2 S or g-C 3 N 4 . [95,96] As a single element layered material, black phosphorus has been intensely investigated as an efficient photocatalyst and electrocatalyst. It has a highly anisotropic electronic structure with a high piezoelectric [70] Copyright 2018, Materials Research Society.…”
Section: D Ultrathin Materialsmentioning
confidence: 99%
“…More accurately, Au or Ag deposition under ultrasonic proved the existing of polarization along [001] direction, as the metals were found to be distributed on the edges of Mo 2 S or g-C 3 N 4 . [95,96] As a single element layered material, black phosphorus has been intensely investigated as an efficient photocatalyst and electrocatalyst. It has a highly anisotropic electronic structure with a high piezoelectric [70] Copyright 2018, Materials Research Society.…”
Section: D Ultrathin Materialsmentioning
confidence: 99%
“…In addition to the auxiliary role that piezopotential plays in piezo‐photocatalysis, piezocatalysis based on the piezoelectric effect alone nowadays demonstrates high‐efficiency in organic synthesis, bio‐applications, water remediation, and small‐molecule catalysis such as the oxygen reduction reaction (ORR), [10] water splitting, [8a] and CO 2 reduction [11] . In these systems, piezoelectric materials with various morphologies, such as discrete powders or 2D films, are dispersed and subjected to external mechanical excitation to trigger the chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been devoted to designing promising photocatalysts, which is the key in determining the H2O2 production performance. Recent studies have demonstrated that metalfree photocatalysts such as graphitic carbon nitrides [9][10][11][12], covalent triazine frameworks [13], polymer-supported carbon dots [14] and graphene oxides [15] are promising photocatalysts for H2O2 production compared to inorganic metal-based photocatalysts [13]. However, metal-free photocatalysts generally possess wide bandgaps and respond to a limited region of the solar spectrum (< 460 nm) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%